STATIC ANALYSIS OF SYMMETRICALLY LAMINATED RECTANGULAR COMPOSITE PLATES WITH DIFFERENT BOUNDARY CONDUTIONS - Altunsaray, Erkin; Bayer, Ismail (YILDIZ TECHNICAL UNIV, 2012)
In this study static analysis of symmetrically laminated rectangular composite plates uniformly lateral loaded are examined. The cases of all edges clamped or all edges simply supported are investigated. Maximum deflections of the symetrically laminated composite plates consisting of different orientation angle types and aspect ratios are examined parametrically by using the Galerkin Method and the Least Square Method based on the governing differential equations of Classical Lamination Plate Theory (CLPT). Results are compared with Finite Element Method (FEM) software package ANSYS. It is observed that results of the Galerkin Method known as a powerful Weighted Residual Method are more consisted with the results of FEM (ANSYS) than the Least Square Method for all boundary conditions.
Keywords: Symmetrically composite plates; static analysis; maximum deflection; classical lamination plate theory (CLPT); weighted residual methods; the Galerkin Method; the least square method; finite element method (FEM) ANSYS; parametric study; VIBRATION; Engineering